Insect World - Time Life Books; Nang Chan Yeema (New York, USA Time Life Books Inc., 1988)
Presents, in question and answer format, information about the behavior, food-gathering, defenses, anatomy, and surprising habits of all kinds of insects.
Keywords: Juvenile Nonfiction